Myocardial bridges of the coronary arteries in the human fetal heart - ÖZDOĞMUŞ, NECMETTİN ÖMER (SPRINGER, 2010)
During the last century, many investigators reported on myocardial bridges in the adult human heart. In the present study, 39 human fetal hearts (the mean gestastional age was 30 weeks) were studied for myocardial bridging, and the results were correlated with adult data. Among the 39 (27 male and 12 female) fetal hearts studied, 26 bridges were observed on 18 fetal hearts (46.2%). Ten of the bridges had one myocardial bridge, whereas double myocardial bridges were observed in eight fetal hearts. The most frequent myocardial bridges were observed on the left anterior descending artery (LAD), which had 13 bridges (50%). Eight (30.7%) myocardial bridges were on the diagonal artery, and on the posterior descending artery there were five (19.3%). Myocardial bridges were not observed on the circumflex artery. The data presented in this study may provide potentially useful information for the preoperative evaluation of the newborn and may have a clinical implication for sudden fetal death.
Keywords: Myocardial bridge; Heart; Fetus; Coronary artery; INTRACORONARY ULTRASOUND; ATHEROSCLEROSIS; ANGIOGRAPHY; INFARCTION